2019
DOI: 10.1002/rfe.1032
|View full text |Cite
|
Sign up to set email alerts
|

Increasing return response to changes in risk

Abstract: Risk aversion theory is based on an individual's choice among risky assets with expected utility in its foundation. It is about investor behavior (i.e., investor choice), under normal circumstances, toward assets with various levels of risk. A positive and marginally diminishing relationship between risk and return exists. This study is about investor behavior related to their response (not choice) to risk. We present an argument and supporting evidence that investors’ return response to risk is increasing wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 60 publications
3
6
0
Order By: Relevance
“…GARCH-M t-Dist. On the other hand, the developed markets findings support the evidence found in previous studies, particularly the US market-Lundblad (2007); Goldman and Shen (2018) and Dicle (2019)-but are contrary to the negative risk premium that has also been observed in the same markets by authors such as Glosten et al (1993); Goyal (2000); Kumar and Dhankar (2010); Aslanidis et al (2016); Wang et al (2017) and Eraker and Wu (2017). The difference may be explained by the different sample period lengths, starting and ending periods and market events covered, methods used and different broad market indices.…”
Section: Gjr-garch-m Gedsupporting
confidence: 90%
See 1 more Smart Citation
“…GARCH-M t-Dist. On the other hand, the developed markets findings support the evidence found in previous studies, particularly the US market-Lundblad (2007); Goldman and Shen (2018) and Dicle (2019)-but are contrary to the negative risk premium that has also been observed in the same markets by authors such as Glosten et al (1993); Goyal (2000); Kumar and Dhankar (2010); Aslanidis et al (2016); Wang et al (2017) and Eraker and Wu (2017). The difference may be explained by the different sample period lengths, starting and ending periods and market events covered, methods used and different broad market indices.…”
Section: Gjr-garch-m Gedsupporting
confidence: 90%
“…They also found that implied volatility could predict future realized variance. On the US market, Dicle (2019), from 2000 to 2017, found that the risk-return relationship was positive in calm, bullish and low-risk markets, but negative in volatile, bearish and high-risk markets. This suggests that investors are less rational in the presence of fear but act more rationally in calmer markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It should be noted, however, that cybercrime victims' total risk-taking level reduces in the short term (i.e., three to six months after the cybercrime), increases in the medium term (i.e., six to twelve months after the cybercrime), and then remains permanently at a level that is higher than the initial risk-taking level in the long term (i.e., after twelve months). This result is consistent with recent literature showing that investor behavior, such as risk appetite, can change over time and that the level of risk-such as the level of risk of falling victim to cybercrime-is itself a determinant of such changes (Dicle, 2019). Further, we conduct a risk decomposition and split total address-level risk-taking into diversifiable and non-diversifiable risk-taking levels per address.…”
Section: About Here]supporting
confidence: 89%
“…This result is consistent with recent literature showing that investor behavior changes over time and that, for example, the perceived risk of fraud can itself be a determinant of risk-taking by investors (Dicle, 2019). To shed light on the dynamics of the treatment effects, we plot the difference-indifference estimates for total risk, non-diversifiable risk, and diversifiable risk in Panels A, B, and C of Figure 3.…”
Section: [Place Table 7 About Here]supporting
confidence: 86%
“…Examining the potential asset pricing implications of shifts in risk aversion, Dicle (2019) shows that daily stock prices have a negative relation with implied volatility. Furthermore, price response to increases in risk levels are greater when investors perceive the risk levels to be higher than "normal" levels and are more fearful.…”
mentioning
confidence: 99%